The influence of hedonic shopping motivation and shopping lifestyle on impulse buying through positive emotion in e-commerce - Mariyana, Mariyana; Djawoto, Djawoto; Suhermin, Suhermin (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2023)
Therefore, this study aimed to examine and analyze the effect of hedonic shopping motivation, and shopping lifestyle, either directly or indirectly through impulse buying in Shopee e-commerce. The data collection technique used purposive sampling. In line with that, there were 95 respondents as the sample. Moreover, the study was descriptive-quantitative with descriptive analysis and statistic inferential, i.e. using SmartPLS 4.0 with bootstrapping test. In addition, both hedonic shopping motivation and shopping lifestyle had a significant effect on positive emotion. However, hedonic shopping, as well as a shopping lifestyle, had an insignificant effect on impulse buying. Likewise, positive emotion proved to mediate both hedonic shopping motivation and shopping lifestyle on impulse buying (full mediation). In other words, positive emotion could improve or determine consumers to have impulse buying in Shopee e-commerce.